Examining dimensions of career intentions: insights from medical and nursing students at a private not-for profit university in Vietnam - Minh Thuy Ha; Huy Cu Dao; Thi Hoa Huyen Nguyen; Hoang Long Nguyen; Phuoc Le (BMC Medical Education)
Abstract Background Understanding students’ career intentions through evidence-based approaches is crucial for developing effective career guidance and intervention strategies. Although there has been considerable attention in this field, research remains limited, particularly in low- and middle-income countries (LMICs) in Asia. These regions have unique socioeconomic conditions and cultural norms that potentially shape decision-making processes. This study provides insights into the career intentions of medical and nursing students and identifies the key determinants influencing their choices at a newly established private institution (VinUniversity) in Vietnam. Methods This study employs a mixed-methods design. The quantitative phase involved a survey of all undergraduate medical and nursing students. The qualitative phase consisted of in-depth 11 individual interviews with a purposive sample until data saturation. Results A total of 198 students (77%) participated in the quantitative phase. The majority of students (75.8%) expressed interest in clinical practice, with preferences notably high for surgical specialties (30.9%), internal medicine (10.1%), and pediatrics (10.1%). 22.7% of students expressed a desire to work overseas, and a significant number (70.7%) indicated the lack of a career guidance program. Qualitative data revealed that personal interest, family influence, financial stability, and societal appreciation were primary influencers in career choice. Discussion The study underscores the complex interplay between personal interests, family influence, financial considerations, and societal expectations in shaping career choices. The persistent low interest in family medicine and primary care continued to be a concern. Conclusion This study provides further insights into the career intentions and influencing factors among medical and nursing students at VinUniversity. The implications for practice include implementing tailored career guidance programs, offering diverse elective tracks that incorporate global health experiences, and establishing structured mentorship programs. It is also recommended to measure the impact of these interventions through longitudinal follow-up studies to enhance career satisfaction, better prepare future healthcare professionals, and contribute to the improvement of healthcare systems.